Contrasting Genetic Diversity and Connectivity at the Eastern Range Edge of the Mediterranean Seagrass ( Posidonia oceanica ) - Daniela Haverbeck; Irene Olivé; Emanuela Dattolo; Mehmet Fatih Huseyinoglu; Paolo G. Albano; Gabriele Procaccini (Marine Ecology, 2025)
Populations at a species' distribution edges often present reduced gene flow, increased impact of genetic drift, and impoverished genetic variation, globally compromising their ability to adapt to environmental changes. This study assessed the genetic diversity, structure, and connectivity of the Mediterranean endemic seagrass Posidonia oceanica at its easternmost distribution limit, from diverse thermal regimes around Cyprus, contextualised within a set of 16 Turkish populations in the Levantine and Aegean Seas (eastern Mediterranean). The genetic assessments were based on sets of 13 to 16 microsatellite loci, depending on the analysis. Our findings revealed lower genotypic and allelic richness in the Cypriot populations, which also presented lower connectivity and higher differentiation among them in comparison to the Turkish ones. Additionally, the genetic and genotypic diversity and the connectivity of Cypriot populations were highly variable, with populations presenting high diversity and connectivity, while others exhibited extremely low diversity and high isolation. The discrepancies among the Cypriot populations were potentially due to differences in the sexual reproductive output related to the different thermal regimes around the island and the presence of barriers to gene flow along the island's southern coastline. This study advances our understanding of the genetic connectivity and genetic diversity of range‐edge P. oceanica populations in the Eastern Mediterranean. This knowledge can guide the management of conservation and ecosystem restoration initiatives for this habitat‐forming seagrass species.

Exploring priming strategies to improve stress resilience of Posidonia oceanica seedlings - I. Provera; M. Martinez; A. Zenone; V.M. Giacalone; G. D'Anna; F. Badalamenti; L. Marín-Guirao; G. Procaccini (Marine Pollution Bulletin, 2024)

The Tropical Seagrass Halophila stipulacea: Reviewing What We Know From Its Native and Invasive Habitats, Alongside Identifying Knowledge Gaps - Gidon Winters; Sven Beer; Demian A. Willette; Inés G. Viana; Kelcie L. Chiquillo; Pedro Beca-Carretero; Betty Villamayor; Tomás Azcárate-García; Rachamim Shem-Tov; Bridget Mwabvu; Luciana Migliore; Alice Rotini; et al. (Frontiers in Marine Science, 2020)

Environmental processes driving anchovy and sardine distribution in a highly variable environment: the role of the coastal structure and riverine input - A. Bonanno; M. Barra; G. Basilone; S. Genovese; P. Rumolo; S. Goncharov; S. Popov; B. Buongiorno Nardelli; D. Iudicone; G. Procaccini; S. Aronica; B. Patti; et al. (Fisheries Oceanography, 2016)
Engraulis encrasicolus and Sardina pilchardus stocks are highly variable in terms of recruitment, biomass and spatial distribution. Changes in habitat conditions may influence both the survival of the early life stages and the adult stages. Detailed studies on the spatial distribution and habitat selection of such species have been performed in different areas of the world, highlighting the importance of environmental processes. The present study analyzes the spatial distribution of anchovy and sardine in the Tyrrhenian Sea in relation to environmental heterogeneity. Four acoustic surveys were carried out in this area in the period 2009–2014. Analysis of the environmental dataset permitted identification, in two specific areas, of a pattern of variables driving enrichment processes and impacting on the habitat suitability of the two species. In the northern and central parts of the study area, both anchovy and sardine showed a marked preference for shallower areas characterized by lower salinity. In these areas, PCA results on an environmental dataset highlighted a strong link between primary production, particulate organic carbon, distance from the mouth of the river, salinity and depth. A less clear picture was obtained for the southern part of the Tyrrhenian sea, characterized by a narrow continental shelf, moderately complex coastline morphology and the presence of very small rivers. Most of the anchovy biomass was found to be located in enclosed areas (gulfs) under the influence of relatively small rivers. This finding, taking into account that the surveys were carried out during the anchovy spawning period, highlights for such species a positive effect of the interaction between coastal morphology and riverine input, probably favoring food supply and retention of spawning products.

Genetic structure in the Mediterranean seagrass Posidonia oceanica : disentangling past vicariance events from contemporary patterns of gene flow - I. A. SERRA; A. M. INNOCENTI; G. DI MAIDA; S. CALVO; M. MIGLIACCIO; E. ZAMBIANCHI; C. PIZZIGALLI; S. ARNAUD-HAOND; C. M. DUARTE; E. A. SERRAO; G. PROCACCINI (Molecular Ecology, 2010)

Phylogeography of the sea urchin Paracentrotus lividus (Lamarck) (Echinodermata:Echinoidea): first insights from the South Tyrrhenian Sea - V. Iuri; F. P. Patti; G. Procaccini (Hydrobiologia, 2007)

Phylogeography of two species of Lysidice (Polychaeta, Eunicidae) associated to the seagrass Posidonia oceanica in the Mediterranean Sea - M. A. Iannotta; F. P. Patti; M. Ambrosino; G. Procaccini; M. C. Gambi (Marine Biology, 2007)

Local genetic structure in a clonal dioecious angiosperm - M. V. RUGGIERO; T. B. H. REUSCH; G. PROCACCINI (Molecular Ecology, 2005)
We used seven microsatellite loci to characterize genetic structure and clonal architecture at three different spatial scales (from meters to centimetres) of a Cymodocea nodosa population . C. nodosa exhibits both sexual reproduction and vegetative propagation by rhizome elongation. Seeds remain buried in the sediment nearby the mother plant in a dormant stage until germination. Seed dispersal potential is therefore expected to be extremely restricted. High clonal diversity (up to 67% of distinct genotypes) and a highly intermingled configuration of genets at different spatial scales were found. No significant differences in genetic structure were found among the three spatial scales, indicating that genetic diversity is evenly distributed along the meadow. Autocorrelation analyses of kinship estimates confirmed the absence of spatial clumping of genets at small spatial scale and the expectations of a very restricted seed dispersal (observed dispersal range 1–21 m) in this species.

Bipolar distribution of the cyst-forming dinoflagellate Polarella glacialis - M. Montresor; C. Lovejoy; L. Orsini; G. Procaccini; S. Roy (Polar Biology, 2003)

Genetic identity and homozygosity in North-Adriatic populations of Posidonia oceanica: An ancient, post-glacial clone? - Maria Valeria Ruggiero; R. Turk; G. Procaccini (Conservation Genetics, 2002)

Spatial patterns of genetic diversity in Posidonia oceanica , an endemic Mediterranean seagrass - G. Procaccini; L. Orsini; M. V. Ruggiero; M. Scardi (Molecular Ecology, 2001)
Posidonia oceanica is an endemic seagrass species in the Mediterranean Sea. In order to assess levels of genetic structure in this species, the microsatellite polymorphism was analysed from meadows collected in several localities, along the coasts of the Tyrrhenian Sea (Mediterranean Sea). The existence of single population units and the recruitment of seedlings collected in some localities were investigated. Moreover, genetic structure at different spatial scales and biogeographic relationships among populations were also assessed. Our analysis showed the existence of clear patterns of genetic structure in P. oceanica in the area considered in the analysis. P. oceanica , in fact, is present in separate meadows that represent discrete populations, characterized by low genetic diversity. Comparable levels of genetic variability between mature meadows and seedlings were found. Patterns of genetic relatedness among populations seem to be in accord with direction of dominant current flux in the whole area, separating South Tyrrhenian from North Tyrrhenian populations. Moderate levels of gene flow between populations and genetic substructure within populations, together with the finding of the limited role of sexual reproduction in increasing genetic variability, should be a cause for concern for the persistence of this essential resource in the Mediterranean basin.

Structural, morphological and genetic variability in Halophila stipulacea (Hydrocharitaceae) populations in the western Mediterranean - G. Procaccini; S. Acunto; P. Famà; F. Maltagliati (Marine Biology, 1999)